Redes sociais na experiência migratória de mulheres venezuelanas em Boa Vista - Roraima - Lopes, Kesy Stheffany Silva (2022)
Considering the expansion of venezuelan migrations to Roraima and the increasing participation of women in recent migratory processes, this work intends to identify the configuration of migratory networks and the process of (re) negotiation gender relations of venezuelan women in a migratory context in Boa Vista. – Roraima. In this way, the discussions will be developed around three central categories, namely: gender, social networks and migrations. This analytical context is justified from the understanding that women participate actively and independently in the construction of migratory projects and even in the articulation and structuring of migratory networks. Thus, the use of gender studies marks a political and reflexive position that focuses on social inequalities based on gender and the way in which these processes are manifested in female migrations. In addition, attention is paid to the issue that men and women experience international migration in different ways and, therefore, the reflections seek to understand what are the challenges posed to venezuelan migrant women before the migration decision itself, during the displacement and after arrival at the receiving society. In this sense, studies on social networks will support the analysis of the strategies developed in the process of confrontation of difficulties, protection and cooperation between women. Semi-structured interviews were carried out with four venezuelan women who lived in Boa Vista, through which it was able to learn about their life stories, difficulties and dilemmas, seeking to know migrations from the reports of migrant women themselves, valuing the way they understood the experiences daily. The results obtained during the field research indicate the direct role of women in the creation, articulation and strengthening of social networks, including migratory networks; point out that, in some cases, there was a (re)negotiation of gender relations through the core role of women in the management of resources and information, in addition to family support. Among other aspects, the results show the need to think about and develop public policies aimed at confronting social inequalities, promoting respect for migrant populations, especially women, guaranteeing opportunities for access to the formal labor market, and that, for and finally, promote safe reception and real possibilities in the life transformations sought by venezuelan migrant women and their families.